The power of money : how governments and banks create money and help us all prosper - Sheard, P. (Ascent Audio, 2023)
Money issues dominate the news, but economic jargon and the complexity of it all can be bamboozling for regular folks. Paul Sheard, a leading economist and research fellow at Harvard Kennedy School, is known for his ability to see the forest and the trees and demystify complex economic phenomena. With The Power of Money, Sheard empowers listeners to become better-informed economic citizens by providing context for some of the biggest questions surrounding money, such as: How does money come into existence? How is the process of money printing governed, particularly if too much of it causes inflation? What is quantitative easing and how does it work? Does government debt ever have to be repaid, and is it really a burden on our grandchildren? Are financial crises bound to happen sometimes? Can the euro, a currency without a government, survive in its current form? Are proposed cures for economic inequality worse than the disease? What is the future of money-are cryptocurrencies going to upend the money system as we know it? Financial enthusiasts and non-specialists alike will be surprised by the answers to these questions. The Power of Money provides a comprehensive foundation of knowledge to help you feel better informed and more confident as you follow and engage in economic and financial affairs and policy debates.